(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital marketing campaigns are put into practice by the companies to promote their business and increase the outcome. The campaigns are designed with innovation and keeping in view the market trends. Corporate culture is also advancing on the new methodologies and digital marketing tools, which will help in development of business. Campaigns made for business enhancement bring new customers as well as increase the value.